2020
DOI: 10.1101/2020.07.25.20161927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathological uptake with 18-Fluorocholine versus 99mTc-MIBI in the location of the parathyroid glands in hyperparathyroidism. Systematic review and meta-analysis

Abstract: Introduction: The location of the pathological parathyroid glands in hyperparathyroidism is usually carried out by means of 99mTc-sestamibi scintigraphy, which increases its precision by adding the ultrasound examination. The non-localization of the parathyroid glands increases the difficulties for surgical removal. To increase the detection of pathological glands, other radioactive tracers are used, such as methionine, fluorocholine or 18F-flurpiridaz. Objective: To establish if PET / CT with 18-Fluorocholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…See Figure 5. In both the selected articles in our meta-analysis and in previous meta-analysis, CH localization studies have shown greater ability to locate pathological glands [34,[42][43][44][45] than MIBI or methionine [46][47][48] in both first exploration and rescue scan [31,49].…”
Section: Resultsmentioning
confidence: 68%
“…See Figure 5. In both the selected articles in our meta-analysis and in previous meta-analysis, CH localization studies have shown greater ability to locate pathological glands [34,[42][43][44][45] than MIBI or methionine [46][47][48] in both first exploration and rescue scan [31,49].…”
Section: Resultsmentioning
confidence: 68%